Pharmacological Stimulation of Phagocytosis Enhances Amyloid Plaque Clearance; Evidence from a Transgenic Mouse Model of ATTR Neuropathy - Fella, Eleni; Sokratous, Kleitos; Papacharalambous, Revekka; Kyriacou, Kyriacos; Phillips, Joy; Sanderson, Sam; Panayiotou, Elena; Kyriakides, Theodoros (Frontiers in Molecular Neuroscience, 2017)
Hereditary ATTR V30M amyloidosis is a lethal autosomal dominant sensorimotor and autonomic neuropathy caused by deposition of aberrant transthyretin (TTR). Immunohistochemical examination of sural nerve biopsies in patients with amyloidotic neuropathy show co-aggregation of TTR with several proteins; including apolipoprotein E, serum amyloid P and components of the complement cascade. Complement activation and macrophages are increasingly recognized to play a crucial role in amyloidogenesis at the tissue bed level. In the current study we test the effect of two C5a receptor agonists and a C5a receptor antagonist (PMX53) on disease phenotype in ATTR V30M mice. Our results indicate that amyloid deposition was significantly reduced following treatment with the C5a receptor agonists, while treatment with the antagonist resulted in a significant increase of amyloid load. Administration of the C5a receptor agonists triggered increased recruitment of phagocytic cells resulting in clearance of amyloid deposits.